2019
DOI: 10.1002/jcsm.12503
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia, long‐term conditions, and multimorbidity: findings from UK Biobank participants

Abstract: Background Sarcopenia, the loss of muscle strength and mass, predicts adverse outcomes and becomes common with age. There is recognition that sarcopenia may occur at younger ages in those with long‐term conditions (LTCs) as well as those with multimorbidity (the presence of two or more LTCs), but their relationships have been little explored. Our aims were to describe the prevalence of sarcopenia in UK Biobank, a large sample of men and women aged 40–70 years, and to explore relationships with different catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
88
3
9

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 40 publications
(60 reference statements)
11
88
3
9
Order By: Relevance
“…Recently the UK Biobank reported a 5.3% prevalence of probable sarcopenia for 40–70 year olds [ 21 ], which differs from the 1.3% prevalence reported in the current study even though our participants were older. This could partly be influenced by instrumental differences, as we used the electronic version of the Jamar dynamometer compared to the hydraulic version commonly used by others.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently the UK Biobank reported a 5.3% prevalence of probable sarcopenia for 40–70 year olds [ 21 ], which differs from the 1.3% prevalence reported in the current study even though our participants were older. This could partly be influenced by instrumental differences, as we used the electronic version of the Jamar dynamometer compared to the hydraulic version commonly used by others.…”
Section: Discussioncontrasting
confidence: 99%
“…We recently found a prevalence of PS defined using weak grip strength in UK Biobank participants aged 60-70 of 8% [25], which is similar to the prevalence of weak grip strength in the present study (7%). In the present study, we saw limited agreement between weak grip strength and slow chair rise time, with only 15% of those with PS having poor performance on both tests.…”
Section: Discussionsupporting
confidence: 90%
“…We used data from a sample in early old age, and this may limit the generalisability of our findings. However, there is growing interest in the identification of sarcopenia in midlife and early old age, especially in the setting of patients with long-term conditions [25]. We also used a different question to assess self-reported strength than the one in the SARC-F tool (see "Methods" section), although given that most participants had an overall score of zero or one, this change would have been unlikely to cause a substantial reduction in the prevalence of participants who were SARC-F positive (a score of greater than or equal to four points).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, past papers have reported that skeletal muscle mass and skeletal muscle strength are maximized in the 20s and 30s [ 63 ], and there is a standard that the target age for sarcopenia is 60 or 65 years [ 3 ]. On the other hand, there are reports targeting people over 40 years old [ 64 ]. Controlling the diet from a young age can prevent various diseases, including the prevention of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%